Research progress on role of saliva samples in tuberculosis diagnosis - Hu, Q F; Liu, Y; Li, Y S; Guo, S L (Zhonghua jiehe he huxi zazhi, 2025)
Tuberculosis is a significant global infectious disease. Accurate diagnosis is vital for achieving the global goal of ending tuberculosis by 2035. In 2014, the World Health Organization released target product profiles for new tuberculosis diagnostics, emphasizing the need for instant, non-sputum-based tests that can detect all tuberculosis forms by identifying specific biomarkers or characteristics. Non-sputum samples like saliva are easier to collect and non-invasive, which is better for special groups (e.g., children, HIV-positive patients, and sputumless patients) than sputum-based tests. Saliva is a promising alternative for tuberculosis diagnosis as it is a non-invasive and information-rich liquid biopsy sample. This paper reviewed the collection of saliva samples, -specific biomarkers, host-derived specific and non-specific markers, and other areas of diagnostic research. It also discussed the challenges of using saliva as an alternative sample for tuberculosis diagnosis and future research directions.